An Analysis of Sentence Length and Pattern of Research Article Discussion Section by International Authors in Applied Linguistics Published in International Journals - Afrizon, Ejontomi; Arsyad, Syafnil; Syafryadin, Syafryadin (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The discussion section of a research article serves to explain and highlight the importance of the study’s results in relation to the existing knowledge surrounding the research problem. This section should be given more attention since the researcher would give his ideas through his own words and sentences. Accordingly, this research attempts to discover the sentence length and pattern in the discussion section of a research article by international authors in applied linguistics published in international journals. The method used in this study was a descriptive qualitative study to discover and describe the data. The total number of articles in this study was 30 from six international accredited journals sites indexed by corpus (Q1). The first result indicated that the most frequent types were Medium and Long sentences. It may imply that the authors are willing to write efficient sentences by combining two or more simple sentences to deliver ideas more informatively. The second result indicated that the most frequent types of sentence patterns were Simple and Complex sentences. The authors tended to make simple sentences to help the readers understand the ideas and thought more easily. The authors created complex sentences to make the discussion more efficient and to avoid the redundant of the same sentences or repetition. The third result indicated that RELC articles had the highest frequency of long sentences among all five different journals. The fourth result indicated that RELC articles had the lowest frequency of simple sentences and a relatively frequent number of complex sentences among the five different journals. In contrast, GEMA articles had the highest frequency of simple sentences and a relatively small number of complex sentences. In conclusion, even though the five journals are classified as Quartile 1, they still had differences.